PEMBUATAN INKUBATOR TUKIK UNTUK KONSERVASI PENYU PANTAI PANGUMBAHAN UJUNG GENTENG - Octaviani, Sandra; Ghozali, Theresia; Basuki, Widodo Widjaja; Wijayanti, Linda; Sereati, Catherine Olivia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Turtles are protected animals because of the emergency of extinction by a lot of conservation of turtle cultivation to increase its population. It is unavoidable if there are still many population reductions from turtles, one of which comes from the low survival rate of baby turtles called hatchlings. The process of laying eggs for female turtles requires warm beach sand to cover their eggs and this occurs at night when the moon is dark. After about two months the eggs will hatch, and the hatchlings usually go straight to the sea. There are many disturbances experienced by hatchlings to get to the sea such as being kidnapped, being preyed upon, and not even going to the sea. Improvements in conservation facilities are made to provide an incubator which are always kept warm by being provided with a bulb as a heater, a thermostat as a temperature regulator and a humidifier as a humidity regulator. After hatching the eggs are placed in a replacement pond which was built as a hatchling pond for temporary shelter for the newly hatched hatchlings, and the pond is placed in a cleaned hatchery room with the roof replaced with a mild steel frame The result of the upgrade from this facility is that hatchling success has increased to 91%, and newly hatched hatchlings can be closely monitored until they are ready to be released into the sea. It is hoped that the turtle population in the world can be maintained so that our children and grandchildren will be able to see the turtles directly. Penyu merupakan hewan yang dilindungi karena darurat akan kepunahannya. Sudah banyak konservasi budidaya penyu untuk meningkatkan populasi penyu. Tetapi tidak dapat dihindari jika masih banyak pengurangan populasi dari penyu, yang salah satunya berasal dari rendahnya tingkat keberhasilan hidup dari bayi penyu yang disebut tukik. Proses bertelur penyu betina memerlukan pasir pantai yang hangat untuk menutupi telur-telurnya dan hal ini terladi pada malam hari saat bulan gelap. Setelah sekitar dua bulan telur akan menetas dan tukik biasanya langsung berjalan menuju ke laut. Banyak gangguan yang dialami oleh tukik untuk bisa sampai ke laut seperti diculik, dimangsa, dan bahkan tidak menuju ke laut. Peningkatan fasilitas konservasi yang dibuat menyediakan ruang inkubator yang senantiasa dipertahankan hangat dengan diberi bohlam sebagai penghangat, thermostat sebagai pengatur suhu dan humidifier sebagai pengatut kelembaban. Setelah telur menetas ditempatkan di kolam pengganti yang dibangun sebagai kolam tukik untuk penampungan sementara bagi tukik yang baru menetas, dan kolam diletakkan dalam ruang tukik yang sudah dibersihkan dengan atap diganti dengan rangka baja ringan. Hasil dari peningkatan dari fasilitas ini adalah keberhasilan penetasan tukik meningkat menjadi 91 %, dan tukik yang baru menetas dapat diawasi dengan seksama sampai siap dilepas ke laut. Diharapkan populasi penyu yang ada di dunia dapat terjaga hingga anak cucu kita nanti dapat melihat langsung penyu yang ada.